Clinical and endoscopist factors associated with post‐colonoscopy colorectal cancer in a population‐based sample. (17th November 2020) - Dossa, Fahima; Sutradhar, Rinku; Saskin, Refik; Hsieh, Eugene; Henry, Pauline; Richardson, Devon P.; Leake, Pierre‐Anthony; Forbes, Shawn S.; Paszat, Lawrence F.; Rabeneck, Linda; Baxter, Nancy N.
Abstract: Aim: Factors associated with verified post‐colonoscopy colorectal cancers (PCCRC) have not been well defined and survival for these patients is not well described. We aimed to assess the association of patient, tumour and endoscopist characteristics with PCCRC. Methods: Using population‐based data, we identified individuals diagnosed with CRC from 1 January 2000 to 31 December 2005 who underwent a colonoscopy within 3 years prior to diagnosis. Detected cancers were those diagnosed ≤6 months following colonoscopy; PCCRC were diagnosed >6 months to ≤3 years following colonoscopy. Post‐colonoscopy and detected cancers were verified through chart review using a hospital‐based simple random sampling frame. We used multivariable conditional logistic regression to determine the association of patient, tumour and endoscopist factors with PCCRC and compared overall survival using Cox proportional hazard models. Results: Using the random sampling frame, we identified 498 patients with PCCRC and 498 with detected CRC; we obtained records and confirmed 367 patients with PCCRC and 412 with detected cancers. In multivariable analysis, patient age (OR 1.01; 95% CI 1.00–1.03) and tumour location (distal vs. proximal OR 0.36; 95% CI 0.25–0.53) were associated with PCCRC; endoscopist quality measures were not significantly associated with PCCRC. We did not find significant differences in overall survival between PCCRC and detected cancers (hazard ratio 1.12; 95% CI 0.92–1.32). Conclusion: Although endoscopic quality measures are important for CRC prevention, endoscopist factors were not associated with PCCRC. This study highlights the need for further research into the role of tumour biology in PCCRC development.